Sharia compliant stock market performance of ASEAN-3 countries: A comparative study with conventional counterparts - Rinaima, Chetrine Alya (2025)
This study investigates the risk-adjusted performance of Shariah-compliant and conventional stock indices in Indonesia, Malaysia, and Singapore from 2017 to 2023. Using a comparative study with a quantitative approach, the research evaluates performance through Risk-Adjusted Return Ratios (Sharpe Ratio, Treynor Ratio, and Jensen Alpha) and the GARCH Model to assess efficiency, risk exposure, and the ability to generate excess returns. A t-test is also conducted to determine whether there are statistically significant differences in returns between the two types of indices, along with MAPE analysis to identify which stocks demonstrate greater resilience. The findings indicate that Shariah-compliant stocks generally exhibit more stable risk-adjusted returns, as reflected in higher Sharpe and Treynor Ratios during certain periods. The Jensen Alpha results reveal that these stocks can generate positive abnormal returns under specific conditions. However, the t-test does not reveal a statistically significant difference in average returns between Shariah and conventional indices. The results of the MAPE analysis suggest that Shariah compliant stocks demonstrate better resilience compared to conventional stocks. These findings are consistent with previous research highlighting the resilience of Shariah-compliant stocks due to their financial screening criteria. This research provides valuable insights for future studies, investors, policymakers, and regulators to enhance the sustainability and competitiveness of Shariah capital markets, particularly by improving diversification strategies and strengthening the regulatory framework.